Avalia????o da influ??ncia do conhecimento sobre sustentabilidade nas atitudes, comportamentos e consumo dos alunos do curso de administra????o de uma universidade privada - Silva, Luciano Sant???Anna da (2017)
Sustainability theme is better understood in situations where individuals reach a higher educational level. In the courses of Business Management the subject has been approached; but not necessarily in a specific discipline; but rather, in a fragmented way, in several courses of the course. The objective of this work is to evaluate the influence of the knowledge about Sustainability of the students of the course of Business Management of a private university of S??o Paulo in their attitudes, behaviors and sustainable consumption. Methodologically, this research is a research of mixed methods, with the use of multiple sources of evidence. The first one, through a bibliographical research on Sustainability, identified the constituent variables of the constructs "Knowledge Level on Sustainability" - in its three dimensions (environmental, social and economic), "Sustainable Attitude", "Sustainable Behavior" and "Sustainable Consumption" in order to structure the research instrument on Sustainability in Higher Education Management. The second stage, through the quantitative method, sought to understand the relationships between the determinant variables and the constructs, to validate the constructs statistically and to determine the influence of the level of knowledge about Sustainability in each of its dimensions, attitudes, behavior and consumption of the students, with their visions, beliefs and attitudes. Based on the responses of 131 students, it was possible to conclude that they understand how the University approaches Sustainability and also can identify the teaching of the theme, even if there is no specific discipline on the subject. Respondents agree that the dissemination of knowledge as well as the rooting of sustainable beliefs and values are relevant factors. It was verified through the Structural Equation Modeling that there is influence between the knowledge of each one of the dimensions of the Triple Bottom Line in the sustainable knowledge, as well as of the sustainable knowledge in the attitude, the behavior and the consumption of the students; however, the influence of attitude on consumption was not confirmed. This dissertation contributes both to the academic community and to society, in order to propose to the researched University, as well as other public or private ones, that include in their PPC some interventions, both through the expansion of the research lines directed to Sustainability, as well as in the implementation of extension activities focused on this theme, aimed at transforming sustainable attitudes into sustainable behaviors and practices of students, acting as citizens.